1993
DOI: 10.1007/bf01744738
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes on cardiac glycogen metabolism in rats

Abstract: The effects of diabetes on myocardial glycogen metabolism in rats were examined and compared with those of fasting. Male Wistar rats were divided into three groups: controls, streptozotocin-induced diabetics, and one-week fasted. Isolated rat hearts were subjected to substrate-free 30-min Langendorff perfusion followed by 60-min working heart perfusion with glucose alone or in combination with insulin or insulin plus beta-hydroxybutyrate (BHB). Myocardial glycogen contents were determined before or 30 min afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…1). In the diabetic heart, glucose usage has been shown to shift away from glycolysis and toward an increased flux through the pentose phosphate pathway (1,8,70,84,105,118). In agreement with those reports, we observed that 13 days of elevated glucose presentation resulted in a significant increase in cardiomyocyte glucose-6-phosphate dehydrogenase (G6PdH) activity ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…1). In the diabetic heart, glucose usage has been shown to shift away from glycolysis and toward an increased flux through the pentose phosphate pathway (1,8,70,84,105,118). In agreement with those reports, we observed that 13 days of elevated glucose presentation resulted in a significant increase in cardiomyocyte glucose-6-phosphate dehydrogenase (G6PdH) activity ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…As glycogen accumulation is a reported characteristic of the diabetic myocardium (11,14,19), we sought to identify evidence of glycophagy activity in left ventricular homogenate tissue from streptozotocin (STZ) -induced diabetic rats. STBD1 expression and GABARAPL1 expression were observed to be higher in diabetic rat hearts (ϳ60 and ϳ 20% increased, respectively, as depicted; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DISTURBED SYSTEMIC GLYCEMIC and insulinemic status elicits cardiomyocyte metabolic stress and altered glucose handling. In diabetes, myocardial glycogen accumulation is evident in humans and in a range of experimental models (8,11,14,19). Cardiac glycogen excess has been linked to hypertrophy, arrhythmias, and contractile dysfunction (3).…”
mentioning
confidence: 99%
“…Insulin also plays an important role in the regulation of glycogen synthesis and protein metabolism. Interestingly, differences in the regulation of these pathways have been reported between the heart and skeletal muscles 27,32,33 . For example, diabetes augments glycogen levels in the heart, but not in skeletal muscles 32,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, differences in the regulation of these pathways have been reported between the heart and skeletal muscles 27,32,33 . For example, diabetes augments glycogen levels in the heart, but not in skeletal muscles 32,34,35 . Thus, differences in the levels of insulin‐signalling intermediates may contribute to the tissue‐specific regulation of these pathways by diabetes.…”
Section: Discussionmentioning
confidence: 99%